2019
DOI: 10.20900/jpbs.20190020
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cognition via Exercise (ICE): Study Protocol for a Multi-Site, Parallel-Group, Single-Blind, Randomized Clinical Trial Examining the Efficacy of Aerobic Exercise to Improve Neurocognition, Daily Functioning, and Biomarkers of Cognitive Change in Individuals with Schizophrenia

Abstract: Individuals with schizophrenia (SZ) display cognitive deficits that have been identified as major determinants of poor functioning and disability, representing a serious public health concern and an important target for interventions. At present, available treatments offer only minimal to moderate benefits to ameliorate cognitive deficits. Thus, there remains an urgent need to identify novel interventions to improve cognition in people with SZ. Emerging evidence from animal and basic human research suggests ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 139 publications
1
11
1
Order By: Relevance
“…Additionally, our results suggest AE is a non-stigmatizing, safe, and nearly side-effect-free intervention, suggesting an intervention profile with a promise for broad dissemination. This view is consistent with the European Psychiatric Association’s position paper and treatment guidelines advocating dissemination of physical activity as part of treatment for individuals with severe mental illness, [ 47 ] as well as previous reports for dissemination among fist-episode patients [ 48 ]. Additionally, within the context of the current COVID-19 pandemic, recent reports suggest AE may help protect against development of severe psychopathology [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, our results suggest AE is a non-stigmatizing, safe, and nearly side-effect-free intervention, suggesting an intervention profile with a promise for broad dissemination. This view is consistent with the European Psychiatric Association’s position paper and treatment guidelines advocating dissemination of physical activity as part of treatment for individuals with severe mental illness, [ 47 ] as well as previous reports for dissemination among fist-episode patients [ 48 ]. Additionally, within the context of the current COVID-19 pandemic, recent reports suggest AE may help protect against development of severe psychopathology [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
“…Future studies should aim to examine the impact of AE on SF among such individuals. Our group recently started a large project that would be able to address some of these limitations [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have not observed this relationship, so it might be still premature to draw definitive conclusions about this issue ( 54 , 55 ). While aerobic exercise related cognitive benefits have been linked to BDNF upregulation, this putative mechanism needs confirmation ( 56 ). Holmen et al ( 57 ) found an association between cardiorespiratory fitness and cognition in schizophrenia patients, but they did not find evidence of BDNF mediating this association.…”
Section: In Patients With Chronic Schizophreniamentioning
confidence: 99%
“…Exercise is a promising new area of intervention for individuals across many stages of psychosis, including for those at clinical high risk for psychosis (CHR). [1][2][3][4][5][6][7][8] Despite the benefits of this new area of intervention, substantially less work has examined unique factors of the CHR population that would have bearing on tailoring an effective, early intervention (i.e., understanding characteristic health and starting fitness levels). 7,[9][10][11] Extant research, however, has relied solely on self-report measures of physical activity to assess fitness, 9,10,[12][13][14] with few exceptions.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has demonstrated that exercise interventions are effective in improving cognitive function 1,4,5,11,19 and neurological function 2,11 for individuals across the psychosis spectrum including, risk mental states, CHR, the first episode of psychosis, and schizophrenia populations. Although existing psychosis literature has established that individuals with psychosis have significantly poorer physical health, 1,6,14,19,20 the evidence regarding the physiological health of individuals at CHR for psychosis is unclear.…”
Section: Introductionmentioning
confidence: 99%